Seed Characteristics and Germination of Garcinia gummi-gutta (L.) Robs - Chacko, K. C.; Chandrasekhara Pillai, P. K. (Indian Forester, 1997)
In a seed germination study conducted with Garcinia gummi-gutta (L.) Robs. (Syn. G. cambogia Desr.) seed coat removal (decoating) before sowing advanced germination and also enhanced cumulative germination from 50% to 90% . The viable seeds with a moisture content of 41.65% failed to germinate on drying to 33.4% which is indicative of the ’recalcitrant’nature of the seed. A seed with a mean oven-dry weight of 0.6109 g had 0.2053 g seed coat and 0.4056 g cotyledons with embryo.